Detailed dynamic, geometric and supraglacial moraine data for Glaciar Pio XI, the only surge-type glacier of the Southern Patagonia Icefield. Issue 73 (19th September 2016) - Wilson, Ryan; Carrión, Daniela; Rivera, Andrés
ABSTRACT: In contrast to the general trend for glaciers of the Southern Patagonia Icefield, Glaciar Pio XI has experienced a large cumulative frontal advance since 1945. In an effort to better understand this advancing behaviour, this paper presents a synoptic analysis of frontal fluctuations (1998–2014), ice velocities (1986–2014), ice-surface elevations (1975–2007) and supraglacial moraines (1945–2014) derived from geospatial datasets. These analyses reveal changes in the ice flow of Glaciar Pio XI's freshwater calving northern terminus and tidewater calving southern terminus over recent decades. Between 1986 and 2000, ice flow speed generally accelerated reaching peaks of >15 m d −1 at the frontal edge of the southern terminus. Following this period, flow speed decreased, reducing to <1 m d −1 for the central part of the southern terminus in 2014, despite advancing to a neoglacial maximum. From 2000 to 2014 the reduction in speed was accompanied by a shift in maximum velocity away from the southern terminus, towards the central glacier trunk. As a result, the northern terminus, which accelerated during this period, represented the new primary flow path in 2014. Notably, the moraine maps presented highlight surges occurring around 1981 and again between 1997 and 2000, marked by arcuate moraine features on the southern terminus.